Quantum molecular dynamics simulations of conjugated polymers - Almeida, A. M. (2002)
The softness of conjugated polymers leads to strong coupling between polymer's electrons and lattice vibrations. Therefore, it is necessary to perform quantum molecular dynamics computer simulations in order to study their electronic and optical properties at molecular level. We have used self-consistent molecular dynamics calculations with interatomic forces evaluated from quantum mechanical calculations at the complete neglect of differential overlap level to discuss some of the issues relating to the electronic processes involved in polydiacetylene and poly(p-phenylene vinylene). Specifically addressed are the charge induced structural changes of the polymer chains and the intra-molecular charge mobility. The change in the chemical potential of individual polymer strands at zero temperature is also discussed. Our results suggest a geometrical distortion in the bond length distribution relative to the uncharged chains which is accompanied by changes in atomic charges at the distortion site. The charge carrier mobility is predicted to depend on the strength of the electric field, in accordance with experiments.